Beyond the hospital doors. Issue 4 (April 2015) - Ayoung-Chee, Patricia R.; Rivara, Frederick P.; Weiser, Thomas; Maier, Ronald V.; Arbabi, Saman
<x xml:space="preserve">Abstract</x> BACKGROUND Elderly trauma patients (TPs) are the fastest growing trauma population, increasing the need for postacute care rehabilitation. For TP, discharge to skilled nursing facilities (SNFs) has been associated with higher 1-year mortality compared with discharge to inpatient rehabilitation facilities (IRFs) or home. The availability of IRF beds has been decreasing, but the proportion occupied by non-TPs, specifically stroke patients (SPs), has increased. We wanted to better characterize trends in trauma discharges and compare them with a population that is equally dependent on postdischarge rehabilitation. We hypothesized that discharge to SNF is rapidly increasing, while discharge to IRF is declining for trauma, but not for SPs. METHODS This is retrospective cohort study of adult trauma and SPs discharged from 2003 to 2009. The National Trauma Data Bank and National Inpatient Sample were used to study TPs and SPs, respectively. RESULTS Falls became the leading cause of injury, and the proportion of older TPs increased from 23% to 30%. Older TPs discharged to SNF increased from 30.7% in 2003 to 40.8% in 2009 (p < 0.001). TPs were 34% (adjusted relative risk [RR], 1.34; 95% confidence interval [CI], 1.15–1.57) more likely to be discharged to an SNF and 36% (adjusted RR, 0.64; 95% CI, 0.48–0.85) less likely to be discharged to an IRF. From 2003 to 2009, SPs were 78% more likely to be discharged to an IRF (adjusted RR, 1.78; 95% CI, 1.74–1.82). The largest absolute increase in SP discharges to IRFs occurred the year following implementation of the stroke center certification program. CONCLUSION For TPs, there was a significant increase in SNF discharges and a decrease in IRF discharges. During the same period, after implementation of stroke center certification, SPs were more likely to be discharged to an IRF. Future research should focus on evaluating which postacute care setting is most effective in providing rehabilitation for TPs and adjusting our discharge efforts to improve long-term outcomes. LEVEL OF EVIDENCE Prognostic and epidemiologic study, level III.